SYMBOLIC CONVERGENCE ANALYSIS OF THE DEMOCRATIC PARTY'S INSTAGRAM ACCOUNT2024 ELECTION CAMPAIGN PERIOD - Hendra Sunandar; Farid Irawan; Edison Bonartua (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study analyzes the use of Symbolic Convergence Theory (SCT) in the digital campaign of the Democratic Party through Instagram during the 2024 election campaign. SCT, developed by Ernest Bormann, provides a framework for understanding how groups or communities create and share meaning through narratives and symbols. In this context, the study aims to identify dominant fantasy themes in the Democratic Party's Instagram content and explore how these themes are used to build group identity and solidarity. The methodology used is qualitative content analysis of the Democratic Party's Instagram posts, with primary data obtained from text, images, videos, and interactions (comments, likes, and shares) on the official Instagram account of the Democratic Party. In-depth interviews with relevant parties involved in the digital campaign, including party members and campaign staff, were also conducted to gain insights into the digital campaign strategies adopted. The results show that the Democratic Party effectively uses narratives and symbols through Instagram to build collective identity and emotional bonds with its followers. Fantasy themes such as "People First," "Gaspol," and efforts to reduce poverty are consistently presented in Instagram content, creating strong resonance among the audience. Additionally, the strategy of active interaction with followers through comments, live streaming, and relevant and engaging content successfully increases engagement and voter loyalty. The study also found that the Democratic Party's digital campaign faces significant challenges in the post-truth era, where misinformation and public opinion polarization are increasing. However, by adopting the principles of transparency, accountability, and integrity in their communication, the Democratic Party has been able to maintain public trust and strengthen support from millennial and Gen Z voters. In conclusion, the use of SCT in the Democratic Party's social media strategy has proven effective in building party identity and influencing public opinion. This study provides new insights into the dynamics of political communication in the digital age and offers practical recommendations for political parties in managing their communication on social media to build stronger relationships with voters and supporters.